2019
DOI: 10.1371/journal.pone.0214570
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic factors associated with overweight and obesity among primary school children in semi-urban areas of mid-western Nigeria

Abstract: Background Many developing countries are in a state of nutritional transition from prevalent under-nutrition to the emergent problem of over-nutrition (overweight and obesity), which is associated with increased morbidity and mortality, and whose complications can persist into adulthood with long-term consequences. However, data are limited on the risk factors for overweight and obesity (O&O) among primary school children, particularly those in rural and semi-urban areas in these countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
(46 reference statements)
2
10
2
2
Order By: Relevance
“…Those with monthly family income more than 6500 Ethiopian birr were 12 times more likely to be overweight than those whose monthly income was below 2500 Ethiopian birr. The finding is consistent with different studies conducted in developing countries [56][57][58][59]. This could be due to those who had high monthly income in developing countries being more likely to take processed, westernized foods and use a vehicle for transport which are unhealthy practices.…”
supporting
confidence: 90%
“…Those with monthly family income more than 6500 Ethiopian birr were 12 times more likely to be overweight than those whose monthly income was below 2500 Ethiopian birr. The finding is consistent with different studies conducted in developing countries [56][57][58][59]. This could be due to those who had high monthly income in developing countries being more likely to take processed, westernized foods and use a vehicle for transport which are unhealthy practices.…”
supporting
confidence: 90%
“…BMI and fortune index were also found to be correlated [9] A lofty incidence of gross and obesity was strongly related to females. This indicates a relation between females, attending commercial schools, good socioeconomic position [2]. [18] concluded that infants under five, mass of an infant at birth, material's age; BMI; social status and area Affar, Dire Dawa, gambela, Harari & Somalia were factors considerably affect underfive infant's nutrition habits in Ethiopia.…”
Section: Introductionmentioning
confidence: 98%
“…[16,17] While genetic factors are estimated to cause more than 40 percent variation in Body Mass Index (BMI), [18,19] environmental factors contribute immensely to obesity epidemic. [20] Studies have showed that socio-demographic variables such as age, sex, education level, wealth and marital status are determinants of obesity [21][22][23][24][25]. Also, unhealthy dietary intake, such as a high intake of re ned carbohydrate foods, saturated fats, sugar, and low dietary bre intake [26][27][28][29] have been shown to be associated with increased rates of overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%